Washed microbiota transplantation improves patients with high blood glucose in South China - Wu, Lei; Li, Man-Qing; Xie, Ya-Ting; Zhang, Qing; Lu, Xin-Jian; Liu, Tao; Lin, Wen-Ying; Xu, Jia-Ting; Wu, Qing-Ping; He, Xing-Xiang (Frontiers in Endocrinology, 2022)
Background and Aims: Although fecal microbiota transplantation (FMT) from healthy donors has been shown to have hypoglycemic effects in animal models of diabetes, its clinical impact in patients with abnormal blood glucose metabolism is unclear, especially in southern Chinese populations. The aim of this study was to investigate the feasibility and efficacy of washed microbiota transplantation (WMT) in the treatment of abnormal blood glucose metabolism in a population in southern China. Methods: The clinical data of patients with different indications who received 1-3 treatments of WMT were retrospectively collected. The changes of blood glucose, blood lipids, blood pressure, liver function and blood routine before and after WMT were compared, such as fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), total cholesterol (TC), triglyceride (TG), systolic blood pressure (SBP), white blood cells (WBC), lymphocytes (LY) and platelets (PLT), etc. Results: A total of 195 patients were included in the First Affiliated Hospital of Guangdong Pharmaceutical University, including 20 patients with high blood glucose and 175 patients with normal blood glucose. WMT has a significant effect in reducing short term blood glucose level (FBG) in patients with high blood glucose (p < 0.05). The fasting blood glucose (FBG) of 72.22% of patients with high blood glucose decreased to normal in a short-term (p < 0.001); In the medium term, there was a significant hypolipidemic (TG) (p = 0.043) effect, long term significant blood pressure lowering (SBP, p = 0.048) effect. Overall, WMT significantly reduced the risk of high risk classes of Atherosclerotic Cardiovascular Disease (ASCVD) in the short term (p = 0.029) and medium-term (p = 0.050). Conclusion: WMT can significantly improve blood glucose in patients with high blood glucose, and there is no long-term elevated risk of blood glucose and ASCVD. FBG levels were significantly reduced in both the short and medium term in patients with high blood glucose treated with WMT. Therefore, the regulation of gut microbiota by WMT may provide a new clinical approach for the treatment of abnormal blood glucose metabolism.